A Rancang Bangun Sistem Pengendalian Kualitas Pada PT. X Balikpapan : Rancang Bangun Sistem Pengendalian Kualitas Pada PT. X Balikpapan - Pratama, Rizky; Muqimuddin; Purba, Arini Anestesia; Putra, Rulliannor Syah (SPECTA Journal of Technology, 2024)
X Balikpapan is a business engaged in furniture production. Based on product defect data in 2022. It is known that there is an average gap between the percentage of the number of product defects which is 13.8% and the product defect standard that has been set on the sofa at 10%. The purpose of this study is to determine the causes of failure that must be handled and proposed countermeasures based on the expert system-based FMEA method. The methods used are FMEA and Expert System that connected to Artificial Intellegence Program. The FMEA method is a database in identifying and analyzing failures that produce a Risk Priority Number (RPN) value. The expert system method as a computer system algorithm to imitate the capabilities transferred from an expert expert to a computer to be stored in memory so that it can consult with the computer. The results of this study are in the form of an expert system website design based on the FMEA method with a percentage of data accuracy of 86.66% from 30 system testing data based on environmental conditions on the type of process failure that has occurred in sofa production which results in the type of failure that must be handled, namely in the assembly production process and the type of process failure, namely plywood or broken wood with the highest RPN value of 216 along with recommendations for efforts The countermeasures, is that before the sofa product is sent to the customer, do a final inspection of the plywood and wood used by means of a sofa durability test with a predetermined maximum load. Make sure there are no weaknesses or damage that can cause rupture of plywood and wood.